Sudut Ilmu Sebagai Upaya Meningkatkan Minat Baca di SDN Kejagan, Kecamatan Trowulan, Mojokerto - Yanda Bara Kusuma; Febi Nour Amaliah; Roiisul Ibaad Aunillah; Bimo Putro Nusuantoro; Muhammad Gilang Zain Assalam; Zumrotul Rosyidah; Ika Yuliana Wati; Nursinta Abadiyah; Ifthar Ramadhana Wahyudi; Agustin Nur Awaliyah; Davina Nasywa Ardelia (Universitas 45 Surabaya, 2024)
This study aims to increase the reading interest of students at SDN Kejagan in Trowulan District, Mojokerto. Based on library visit data in April 2024, it was recorded that the level of visits was very low, especially in the upper classes. The